Molecular Profile of Integrase gene intI and Carbapenem gene in Aeromonas sobria Isolates (Medico Legal Update, 2021)
The current study includes the detection of Aeromonas sobria isolates were obtained from total 157 samplesinvolved the clinical samples (diarrhea samples) from patients suffering from diarrheal infections during theperiod from April 2017 to November 2017. at AL-Central Health Laboratory in Najaf governorate. Theseisolates were diagnosed by four method as (Culture method, biochemical tests, Vitek@2GN cards systemand Polymerase chain reaction (PCR) technique). TheVitek@2GN cards system was the best method fordiagnosis, which have led to isolate and diagnosis of 33 isolate. Multidrug resistance (MDR) of bacteriawere detected by MIC testing and performed with the automated VITEK@2 GN/AST compact system.A clear variation was observed in their susceptibility to 13 antibiotics disks, these isolates of A.sobriawere revealed resistance for some antibiotics such as Penicillin class Methicillin, Amoxicillin, Ampicillin,Penicillin (100%), and (91.6%) for Carbenicillin, and high rates of resistance (100%) to Cephalosporinsthat represented by Ceftazidime, Cefotaxime, Cefoxitin and Cefepime. The investigation of mobile geneticelements among isolates demonstrated thatA.sobria have been Class I integron genes (class 1 integronrepresented by integrase intI1, and IMP genes).